HUBUNGAN POWER OTOT TUNGKAI DENGAN KECEPATAN LARI JARAK PENDEK 100 METER SISWA KELAS VIIIa PUTRA SMPN 9 TAPUNG - Ardiansyah, Ryan; Ramadi, Ramadi; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract : This study aims to determine whether there is a correlation between leg muscle power and short-distance running speed of 100 meters of grade VIIIa male students of Junior High School 9 Tapung.  This research is correlation research, the population in this study is grade VIIIa male students of Junior High School 9 tapung, the sample in this study amounted to 15 people.  The sample technique used is total sampling, where all populations are sampled. Thus the sample in this study amounted to a sample of 15 class VIIIa male students of Junior High School 9 Tapung. After that, the data is processed statistically, to test normality with the lilifors test and correlation at a significant level  (0.05). The first analysis between leg muscle power (X1) with the running speed of 100 meters of class VIIIa male students of 9 Junior High School Tapung (Y)  , where rtab at a significant level  (0.05) = 0.532 which rcount (0.161)> rtab (0.532), it means that the hypothesis is accepted and there is no strong relationship between leg muscle power and short-distance running speed of 100 meters, the second analysis is the relationship between leg muscle power (X1) and short-distance running speed of 100 meters (Y) was obtained, where rtab at a significant level  (0.05) = 0.532, which rcount (0.161)> rtab (0.532).  It can be concluded that the relationship between (X1) and (Y) or the relationship between leg muscle power and the running speed of 100 meters of grade VIIIa male students of  Junior High School 9 Tapung is significant. Key Words: Power and Speed